A perspective on novel cascading algal biomethane biorefinery systems. (May 2020) - Bose, Archishman; O'Shea, Richard; Lin, Richen; Murphy, Jerry D.
Graphical abstract: Highlights: Possibilities of utilising microalgae for biomethane generation are investigated. A decision tree for microalgae biorefinery is developed focussed on biomass composition. Multiple configurations of a cascading algal biomethane-biorefinery system (CABBS) are proposed. Techno-economic, sustainability and practical perspectives discussed. Abstract: Synergistic opportunities to combine biomethane production via anaerobic digestion whilst cultivating microalgae have been previously suggested in literature. While biomethane is a promising and flexible renewable energy vector, microalgae are increasingly gaining importance as an alternate source of food and/or feed, chemicals and energy for advanced biofuels. However, simultaneously achieving, grid quality biomethane, effective microalgal digestate treatment, high microalgae growth rate, and the most sustainable use of the algal biomass is a major challenge. In this regard, the present paper proposes multiple configurations of an innovative Cascading Algal Biomethane-Biorefinery System (CABBS) using a novel two-step bubble column-photobioreactor photosynthetic biogas upgrading technology. To overcome the limitations in choice of microalgae for optimal system operation, a microalgae composition based biorefinery decision tree has also been conceptualised to maximise profitability. Techno-economic, environmental and practical aspects have been discussed to provide a comprehensive perspective of the proposed systems.